2014
DOI: 10.1134/s0021894414050058
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of nonlinear processes in a swept-wing boundary layer at the mach number M=2

Abstract: Results of experiments aimed at studying the linear and nonlinear stages of the development of natural disturbances in the boundary layer on a swept wing at supersonic velocities are presented. The experiments are performed on a swept wing model with a lens-shaped airfoil, leadingedge sweep angle of 45 • , and relative thickness of 3%. The disturbances in the flow are recorded by a constant-temperature hot-wire anemometer. For determining the nonlinear interaction of disturbances, the kurtosis and skewness are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…14 To avoid this and to achieve prolongation of the linear stage in the developing disturbance, two new swept wing models (one for natural experiments and another for controlled experiments 15 ) were made with the same level of surface curvature, but with reduced thickness of 3% thickness of the profile. Experiments 14,16,17 under natural conditions performed at M = 2 and low unit Reynolds numbers have revealed that the distance from the leading edge to the onset of transition increased several times in comparison with the above mentioned experiments. 13 This enables investigating the details of the evolution of disturbances in the supersonic boundary layer on swept wing, both in a controlled and natural experiment.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…14 To avoid this and to achieve prolongation of the linear stage in the developing disturbance, two new swept wing models (one for natural experiments and another for controlled experiments 15 ) were made with the same level of surface curvature, but with reduced thickness of 3% thickness of the profile. Experiments 14,16,17 under natural conditions performed at M = 2 and low unit Reynolds numbers have revealed that the distance from the leading edge to the onset of transition increased several times in comparison with the above mentioned experiments. 13 This enables investigating the details of the evolution of disturbances in the supersonic boundary layer on swept wing, both in a controlled and natural experiment.…”
Section: Introductionmentioning
confidence: 60%
“…18 This research is a continuation of a series of experimental studies of the origin of turbulence on the swept wing (Figure 1) in a supersonic flow. 14,16,17,19,20 The results of these studies will be useful in the creation of modern engineering methods for predicting the position of the laminar-turbulent transition.
Figure 1.Swept wing model: (a) top view; (b) aerofoil.
…”
Section: Introductionmentioning
confidence: 99%